Factors Affecting Filling of the Initial Assessment in Inpatience At Putri Hijau Hospital Medan - Muhammad Adiul Ilham; Dilla Fitria; Julita Arnis; Manisha Manisha; Muhammad Gilang Irsandi (Lembaga Pengembangan Kinerja Dosen, 2025)
The issue of improving the quality of health services is a major focus for hospitals in their efforts to provide effective, efficient, and patient-safety-oriented services. One important indicator in improving the quality of nursing services is the process of completing the initial patient assessment, as this stage forms the basis for planning and implementing further nursing actions. This study aims to identify and analyze the factors that influence the initial assessment process at Putri Hijau Hospital in Medan in 2022. The research method used was quantitative with an analytical survey approach and a cross-sectional design. The research population included 135 nurses working in the inpatient ward, while the research sample consisted of 57 nurses selected using incidental sampling techniques. Data collection was carried out using a structured questionnaire that measured the variables of nurses' abilities, skills, attitudes, and motivation. The data were analyzed using univariate and bivariate analyses with the Chi-Square statistical test to determine the relationship between variables. The results showed that the factors of competence and skills (p = 0.002), attitude (p = 0.000), and motivation (p = 0.013) had a significant effect on the completeness and accuracy of the initial assessment of inpatients. These findings illustrate that nurses with high technical competence, positive attitudes, and strong motivation are better able to carry out initial assessments quickly and accurately. Based on these results, it is recommended that hospital management improve continuing education programs, conduct regular supervision, and provide performance-based rewards to strengthen nurses' motivation and professionalism in carrying out optimal initial assessments of patients.